Factors influencing follow-up care post-TIA and minor stroke: a qualitative study using the theoretical domains framework - Turner, Grace M.; Aquino, Maria Raisa Jessica V.; Atkins, Lou; Foy, Robbie; Mant, Jonathan; Calvert, Melanie (BMC health services research, 2022)
Background Follow-up care after transient ischaemic attack (TIA) and minor stroke has been found to be sub-optimal, with individuals often feeling abandoned. We aimed to explore factors influencing holistic follow-up care after TIA and minor stroke. Methods Qualitative semi-structured interviews with 24 healthcare providers (HCPs): 5 stroke doctors, 4 nurses, 9 allied health professionals and 6 general practitioners. Participants were recruited from three TIA clinics, seven general practices and one community care trust in the West Midlands, England. Interview transcripts were deductively coded using the Theoretical Domains Framework and themes were generated from coded data. Results There was no clear pathway for supporting people with TIA or minor stroke after rapid specialist review in hospital; consequently, these patients had limited access to HCPs from all settings (‘Environmental context and resources’). There was lack of understanding of potential needs post-TIA/minor stroke, in particular residual problems such as anxiety/fatigue (‘Knowledge’). Identification and management of needs was largely influenced by HCPs’ perceived role, professional training (‘Social professional role and identity’) and time constraints (‘Environmental context and resources’). Follow-up was often passive – with onerous on patients to seek support – and predominantly focused on acute medical management (‘Intentions’/‘Goal’). Conclusions Follow-up care post-TIA/minor stroke is currently sub-optimal. Through identifying factors which influence follow-up, we can inform guidelines and practical strategies to improve holistic healthcare.